The impact of the COVID-19 pandemic on HIV-positive men who have sex with men: (dis)connection to social, sexual, and health networks. Issue 1 (2nd January 2023) - Cascalheira, Cory J.; Morrison, Corey; D'Angelo, Alexa B.; Garcia Villanueva, Oziel; Grov, Christian
ABSTRACT: The COVID-19 pandemic has disproportionately affected HIV-positive cisgender men who have sex with men (MSM). Between May and June in 2020, we conducted one-on-one semi-structured qualitative interviews with 20 HIV-positive MSM aiming to describe their (dis)connection to social, sexual, and health networks during the COVID-19 pandemic. All participants relied on social support networks to manage pandemic-based distress, using computer-mediated communication as well as physical proximity. To connect to sexual networks, this sample described adaptations to their partner selection strategies, such as enumerating harm reduction approaches. To connect to health networks, participants depended on reassuring providers, resourceful case managers, telehealth, and streamlined access to their antiretroviral therapy (ART) medications. Nonetheless, stay-at-home recommendations reduced community connection, sexual activity, and healthcare access for many participants, and perceptions of these losses were shaped by psychosocial burdens (e.g. loneliness), structural burdens (e.g. environmental barriers, financial difficulties), and health-protective factors (e.g. hopeful outlook, adherence to a regular routine). The COVID-19 pandemic appears to have exacerbated health-related issues for HIV-positive MSM. Given the ongoing COVID-19 mutations, community-based organisations, clinicians, and researchers might use these findings to modify HIV prevention and intervention efforts.